1979
DOI: 10.1021/jm00190a011
|View full text |Cite
|
Sign up to set email alerts
|

Antianaphylactic agents. 1. 2-(Acylamino)oxazoles

Abstract: The synthesis and biological properties of 35 2-(acylamino)oxazoles are described. The majority of the compounds inhibit the release of slow-reacting substance of anaphylaxis (SRS-A) in vitro from sensitized guinea pig chopped lung. In addition, several of the compounds inhibited the release of SRS-A from passively sensitized human chopped lung and protected guinea pigs from the effects of anaphylaxis in a modified Herxheimer test.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
1

Year Published

1981
1981
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(12 citation statements)
references
References 5 publications
0
11
1
Order By: Relevance
“…In contrast to the findings of Greenwood (1982) and Ross et al (1979), who used sensitized guinea-pig and human chopped lung preparations to study the effect of ketotifen on antigen-induced histamine and SRS-A release, we failed to find any inhibition of the antigen-induced mediator release by ketotifen. Apart from differences in immunization procedures, species used and experimental conditions, much higher ketotifen concentrations (10-4 mol 1-1) were used compared to the more appropriate concentrations (500 ngml-' = 1.18 x 10-6moI 1-P) in our experiments, which may explain this discrepancy.…”
Section: Discussioncontrasting
confidence: 52%
See 2 more Smart Citations
“…In contrast to the findings of Greenwood (1982) and Ross et al (1979), who used sensitized guinea-pig and human chopped lung preparations to study the effect of ketotifen on antigen-induced histamine and SRS-A release, we failed to find any inhibition of the antigen-induced mediator release by ketotifen. Apart from differences in immunization procedures, species used and experimental conditions, much higher ketotifen concentrations (10-4 mol 1-1) were used compared to the more appropriate concentrations (500 ngml-' = 1.18 x 10-6moI 1-P) in our experiments, which may explain this discrepancy.…”
Section: Discussioncontrasting
confidence: 52%
“…Although reversal and prevention of P-adrenoceptor-mediated tachyphylaxis (Bretz et al, 1983) might be a very relevant, additional factor for the anti-asthmatic activity of ketotifen in the clinical situation, it does not play a role in our present experiments. Taking into account the fact that ketotifen is a strong histamine Hi-receptor antagonist (Martin & Romer, 1978) and also exhibits functional SRS-A antagonism in vivo (Ross et al, 1979), and the finding in our experiments that ketotifen effectively inhibited the 5-HT induced bronchoconstriction without affecting the mediator re lease, it can be assumed that the bronchoprotective effect of ketotifen is mainly based on (multiple) receptor antagonism. …”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In a compari- son of the effects of ketotifen on anaphy laxis-induced mediator release from gui nea pig and human chopped lung, Ross et al [44] found that, whilst ketotifen inhibits leukotriene release in both species, its ac tivity in human lung is greater. Histamine release is also moderately inhibited in gui nea pig lung, but to a lesser extent in hu man lung.…”
Section: Mediator Releasementioning
confidence: 99%
“…Both are H, an tihistamines and have been shown to pre vent antigen-mediated histamine release in a variety of animal experimental models Roemer, 1977, 1978;Awouters et al, 1977;Borgers et al, 1978]. Evidence for their antianaphylactic action on isolated human tissues is, however, sparse [Kumagai and Tomioka, 1978;Ross et al, 1979] or, in the case of oxatomide, lacking. The aim of the present study is to examine, on hu man cells and tissue (leukocytes and pas sively sensitized chopped lung), the ability of these new antiallergic drugs to inhibit an tigen-mediated histamine release.…”
Section: Introductionmentioning
confidence: 99%